Case Report: A rare case of early esophageal basaloid squamous cell carcinoma with ductal differentiation - Qi, Xing; Zuo, Zhenxiang; Li, Guangchun; Cui, Xiujie; Wu, Honglei (Frontiers in Oncology, 2025)
BackgroundEarly esophageal basaloid squamous cell carcinoma (EBSCC) with ductal differentiation is a rare variant of esophageal cancer (EC), for which the clinical behavior, endoscopic features and diagnostic criteria are not fully elucidated.Case presentationAn 81-year-old female presented to our hospital with a year of eating obstruction sensation. A rough, superficial-elevated and circumferential 1/2 esophageal lesion on the upper esophagus was found by the white light endoscopy (WLE). The uplift and swelling caused by subepithelial lesions suggest that this lesion may infiltrate into the submucosa. Under the narrow band imaging magnifying endoscopy (NBI-ME), papillary-like structures were visible in the lesion, and the loop capillaries classified as intraepithelial papillary capillary loop (IPCL) of type B1 were observed. Furthermore, a fine network pattern of microvascular similar to the surface glandular structure in early differentiated gastric cancer can be seen in the middle of type B1, indicating that the presence of special glandular tubular-like components. Microscopically, the tumor was a poorly differentiated EBSCC with a glandular structure. In addition, the tubular structures transitional with the surface squamous cell carcinoma. Immunohistochemical results showed that the bilayer-tubular structures exhibited bidirectional differentiation towards the outer basal epithelium and the inner columnar epithelium. The double-layer epithelium cells of the tumorous tubules expressed CK7, and the outer cells expressed p40, CK5/6.ConclusionEarly EBSCC with ductal differentiation has unique endoscopic, histological and immunophenotypic characteristics. Understanding of the endoscopic and pathological features of the early EBSCC with ductal differentiation is crucial for early detection, accurate diagnosis, timely treatment, and prevention of misdiagnosis.